Modern trends in the development of selection of vegetable and melon crops - V. F. Pivovarov; A. V. Soldatenko; O. N. Pyshnaya; L. K. Gurkina; E. V. Pinchuk (Овощи России, 2022)
The article reflects the issues of the current state of scientific research in the FSBSI FSVC, directions and prospects for the development of selection and seed production of vegetable crops are shown. Varieties have been created that realize the bioclimatic potential of the cultivation zone, meet market requirements, and are capable of producing high yields under the influence of biotic and abiotic stressors. Selection is carried out in a combination of classical methods with innovative technologies.Biotechnologists have improved the basic protocol for in vitro microspore culture for the Brassicaceae, stages of technology for obtaining doubled haploids in microspore culture in vitro for the Apiaceae are being developed. For the first time, an effective protocol for obtaining double haploids of European radish has been developed. Doubled haploids of vegetable crops of the Cucurbitaceae, Amarantháceae, Amaryllidáceae were obtained in vitro in the culture of unpollinated ovules. The Center conducts research on the increased content of biologically active substances and antioxidants. An important place is occupied by immunological studies on the resistance of vegetable crops to harmful diseases. The institution develops systems of protective measures against pests, diseases and weeds for vegetable crops based on the use of new environmentally friendly preparations. On the basis of fundamental and priority applied research of previous years, the creation of 21 varieties and hybrids of cabbage, table beet, tomato, sweet pepper, onion, chives, leek, cucumber, melon, lettuce, chervil, potato, aster, lychnis has been completed. Along with the creation of new breeding achievements, technologies for their cultivation are being improved through the use of new agricultural practices, microfertilizers, biological products and humates on vegetable crops in various soil and climatic zones of Russia. New agricultural methods are being developed in the cultivation of mushrooms. In the field of seed production, methods are being developed to increase the germination of seeds, seed production, elements of the technology for the production of mother liquors and seeds of various vegetable and melon crops; zonal seed production technologies that increase their yield. In 2021, a team of scientists received an award from the Government of the Russian Federation for scientific work "Development and implementation of innovative technologies for growing vegetables and potatoes to provide the population with environmentally friendly food".